Betriebliche Reorganisation, Entlohnung und Beschäftigungsstabilität - Lutz Bellmann; Thomas Cornelißen; Olaf Hübler; André Pahnke (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2008)
– This article analyses the effects of firm reorganisation on wages and job mobility at individual level. The analysis is based on German linked employer-employee data (LIAB), which combines firm survey data and employee data from the German Federal Employment Services. The period of observation is from 1996 to 2003. The results from fixed-effects estimates differ markedly by skill group and occupational group. For some groups, the introduction of teamwork is associated with higher wages and more job stability. The reorganisation of departments and changes in the shares of external production and in-house production of inputs raise wages for some groups of employees. Transfers of responsibilities to subordinates, however, bring about negative wage effects for some groups of employees. Negative wage effects are also found when firms introduced profit centres. Measures to ensure product quality have mixed effects on wages. In sum, positive effects on wages and job stability were identified more frequently for groups with medium or high skills. This suggests that organisational change is skillbiased. However, clear negative effects on the job stability of the low-skilled could not be found in this analysis. The results also suggest that organisational change generally either impacts on wages or on job mobility, but not on both. Organisational change is found to have an effect on job mobility alone more often than on wages alone. Furthermore, its indirect effect on job mobility via wages is small. The effects of organisational change on wages are more often positive than negative. Negative and positive effects on job mobility are equally frequent.
Keywords: 330; organisatorischer Wandel - Auswirkungen; Lohnhöhe; Beschäftigungsdauer; Gruppenarbeit; Qualitätskontrolle; IAB-Betriebspanel